A marine accident analysing model to evaluate potential operational causes in cargo ships. (February 2017) - Akyuz, Emre
Highlights: A hybrid marine accident analysing model is developed to enhance safety. Quantification of HFACS is provided by integrating ANP method. A marine accident prevention plan is recommended. A serious gas leak incident is analysed. Abstract: This paper introduces a novel hybrid approach to assess potential operational contingencies in a real shipboard accident since safety at sea is of paramount significance in maritime transportation industry. The hybrid accident analysis model integrates an Analytical Network Process (ANP) method with Human Factors Analysis and Classification System (HFACS). To achieve this purpose, the HFACS model provides a schematic conceptual framework to investigate and analyse role of human error in marine accident and the ANP method provides correlation among the factors for assessment. Thus, the most important factors that contribute to the accident are revealed respectively. The novelty of this paper is to present a different perspective during marine accident analysis in which priority weights of accident causes related to the human error are calculated by ANP model. The hybrid accident analysis model is established to enhance safety and prevent loss of life or injury in maritime transportation industry. The proposed hybrid approach is illustrated with a real-ship incident case: a serious liquefied petroleum gas leak from the gas carrier ship. In conclusion, the research is expected to encourage safety researchers and ship-management companies to prevent similar accident occurrence.